Taohong Siwu Decoction Ameliorates Ischemic Stroke Injury Via Suppressing Pyroptosis - Mengmeng Wang; Mengmeng Wang; Zhuqing Liu; Zhuqing Liu; Shoushan Hu; Shoushan Hu; Xianchun Duan; Yanyan Zhang; Can Peng; Can Peng; Daiyin Peng; Daiyin Peng; et al. (Frontiers Media S.A., 2020)
Objective: Taohong Siwu decoction (THSWD) is one of the classic prescriptions for promoting blood circulation and removing blood stasis, and it has a good therapeutic effect on ischemic stroke. We sought to explore the therapeutic effects of THSWD on pyroptosis in rats with middle cerebral artery occlusion-reperfusion (MCAO/R).Methods: MCAO/R model of rats were established by suture-occluded method. MCAO/R rats were randomly divided into five groups, which were model group, nimodipine group, THSWD high, medium and low dose group (18, 9, and 4.5 g/kg, respectively), rats of sham group without thread embolus. All rats were treated by intragastric administration for 7 days. We detected the level of inflammatory factors. NLRP3 and Caspase-1 were detected by immunofluorescence. Western blot was used to detect NLRP3, Caspase-1, ASC, and GSDMD in penumbra. Also, the expression of TXNIP, HMGB1, toll-like receptors (TLR4), NF-κB, and MAPK were detected.Results: THSWD treatment improved the behavioral function and brain pathological damage. These results showed that the levels of TNF-α, TGF-β, IL-2, IL-6, IL-1β, and IL-18 were significantly reduced in THSWD treatment groups. THSWD could significantly decrease the expression levels of NLRP3, Caspase-1, Caspase-1 p10, ASC, TXNIP, GSDMD, HMGB1, TLR4/NFκB, p38 MAPK, and JNK in penumbra.Conclusion: Our results showed that THSWD could reduce the activation level of NLRP3 inflammatory corpuscle, down-regulate GSDMD, and inhibit pyroptosis in MCAO/R rats. These may be affected by inhibiting HMGB1/TLR4/NFκB, MAPK signaling pathways.